DINAMIKA TEKS DAN KONTEKS: MODEL DIALEKTIKA ALQUR’AN DAN REALITAS - Supriyanto Supriyanto (UIN Raden Mas Said Surakarta, 2019)
This study tries to article tries to discuss and mapping the dialectical models between text and reality in the daily human life. 'Limitations' of the text and the development of the time,requires Qur’an to be able to dialogue with the context of space and time. So that,the message of the Qur’an can be understood by human beings, in various dimensions of space and time. One of the Qur'anic communication models with the times is throughthe dialectical model. With the content analysis method, based on the Mushaf Utsmani as its reference, the results show, that there are at least Eleven dialectical models offered by the Qur'an, namely: Alsibr wa Altaqsim (breaking and showingthe opponents' opinions), Istifham Taqriri (questions that have one answer to the truth), Qiyas Mudhmar (Enthimeme), Qiyas Khalaf (Syllogism per Impossible), Qiyas Tamtsil (Reasoning by Analogy), Istidlal by using stories, Altaslim (Presupposition), Almunaqadhah (Refutation), Dalik Alikhtira' and Dalil Alhuduts (the argument which shows everything has its creator), and the continued Dalil. One of the philosophical functions that can be applied with these various dialectical models areto strengthen the argument for the truth of life in the hereafter.